2005
DOI: 10.1086/497283
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Kinematics of the Oxygen‐rich Supernova Remnant G292.0+1.8: Ejecta Shells, Fast‐moving Knots, and Shocked Circumstellar Material

Abstract: We present the results of an in-depth optical study of the core-collapse supernova remnant G292.0+1.8 using the Rutgers Fabry-Perot (RFP) imaging spectrometer. Our observations provide a detailed picture of the supernova remnant in the emission lines of [O iii] k5007, H , and [N ii] k6548. The [O iii] Fabry-Perot scans reveal a bright crescent-shaped spur of previously known high-velocity (V radial $ 1500 km s À1 ) O-rich ejecta located on the eastern side of the remnant. The spur consists of a semicoherent st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
92
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(121 citation statements)
references
References 47 publications
28
92
1
Order By: Relevance
“…This is consistent (based on the discussion in Section 4.1) with a higher overall density in Region 7 than Region 4. (Ghavamian et al 2005), and was shown by Park et al (2002) …”
Section: Mips 70/24 Ratiosmentioning
confidence: 90%
See 3 more Smart Citations
“…This is consistent (based on the discussion in Section 4.1) with a higher overall density in Region 7 than Region 4. (Ghavamian et al 2005), and was shown by Park et al (2002) …”
Section: Mips 70/24 Ratiosmentioning
confidence: 90%
“…Overall, the regions with the hottest dust in Figure 5 are (not surprisingly) Regions 15, 17, and 18, corresponding to the brightest clumps in the Chandra image of G292.0+1.8. Park et al (2002) found that the equatorial belt (Region 15) had a higher density and slightly lower temperature than the outer shell of G292.0+1.8, while Ghavamian et al (2005) detected faint [O iii] λ5007 emission from the belt. This indicates that the elevated density in the equatorial belt in Region 15 has caused the shocks to become partially radiative at that location.…”
Section: Mips 70/24 Ratiosmentioning
confidence: 99%
See 2 more Smart Citations
“…The X-ray spectrum is modeled with a simple power law, although, as with Vela, (and many other sources) the fit to the data is not unique. From the motions of oxygen-rich optical knots and the size of the remnant, Ghavamian, Hughes, and Williams (2005) recently esti-mated a kinematic age for SNR 292.0+1.8 of 3000-3400 years assuming a distance of 6 kpc. This value is in good agreement with the pulsar spin-down age of 2900 years.…”
Section: Snr 2920+18mentioning
confidence: 99%